Awareness of risk factors, symptoms and screening of breast cancer: A cross-sectional survey among 35–65-year-old women in Alappuzha district, Kerala, India - Reshmy Mohan; Jissa Vinoda Thulaseedharan (Journal of Family Medicine and Primary Care, 2023)
Background: Breast cancer awareness is vital to enhance early detection and treatment, thus improving women’s quality of life and reducing the breast cancer burden in a country. This paper describes breast cancer awareness among women in the Alappuzha district, Kerala. Methods: A community-based cross-sectional survey was conducted among 320 women aged 35–65 using a multi-stage cluster-sampling method. The data were collected using a structured interview schedule and analysed using IBM SPSS Statistics-25. The Chi-square test was used to test associations, and binary logistic regression was used to estimate odds ratios and 95% confidence intervals. Results: The most reported risk factor and symptoms were unhealthy food habits (29.6%) and breast lumps (91.7%), respectively. Nearly half of the women spoke about at least one risk factor (53.8%), and 39.8% mentioned at least two symptoms of breast cancer. Awareness of breast self-examination and mammography were 85.7% and 39.5%, respectively. Compared to women with a primary level of education, women with a higher secondary or above level of education were more likely to report at least one risk factor (AOR = 8.96; 95%CI: 3.44-23.36), more than two symptoms (AOR = 4.73; 95%CI: 1.82-12.27) and mammogram as a screening method (AOR = 61.1; 95%CI: 6.56-394.63). Women detected with breast cancer (n = 6) were excluded from the analysis. Conclusion: Women are unaware of most of the risk factors and symptoms of breast cancer, and breast cancer awareness are highly associated with women’s education. Breast cancer awareness creation is essential to improve the early detection of breast cancer among women, especially in the low socioeconomic strata.